2007
DOI: 10.1109/tasc.2007.898608
|View full text |Cite
|
Sign up to set email alerts
|

Study of LR-Loading Technique for Low-Power Single Flux Quantum Circuits

Abstract: A single-flux-quantum (SFQ) circuit is thought to be very suitable as a peripheral circuit for superconducting quantum bits (qubits), which can manipulate and detect the qubit state at a temperature state similar to qubits. Even though the power consumption of SFQ circuits is extremely small, it is still sufficient to heat the substrate at a temperature below 1 K. We have investigated and demonstrated low-power SFQ circuits for this application, using the LR-loading technique, which can reduce the static power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…S UPERCONDUCTING circuits can perform logic operations with extremely high energy efficiency compared to semiconductor CMOS integrated circuits [1], [2]. However, because superconducting circuits such as the single-flux-quantum (SFQ) circuit [3], [4] and its modified versions [5], [6], [7], [8], [9], use the magnetic flux quantum as the information carrier, superconducting circuits are sensitive to external magnetic flux. Magnetic flux trapped inside the superconducting circuit affects the circuit operation [10].…”
Section: Introductionmentioning
confidence: 99%
“…S UPERCONDUCTING circuits can perform logic operations with extremely high energy efficiency compared to semiconductor CMOS integrated circuits [1], [2]. However, because superconducting circuits such as the single-flux-quantum (SFQ) circuit [3], [4] and its modified versions [5], [6], [7], [8], [9], use the magnetic flux quantum as the information carrier, superconducting circuits are sensitive to external magnetic flux. Magnetic flux trapped inside the superconducting circuit affects the circuit operation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Research results have shown that a 16-bit butterfly processing circuit using CMOS can operate at a power of 2.17 mW at frequencies of 100 MHz, and the energy per operation is calculated to be 21.7×10 −12 J [13]. By introducing low-power techniques such as LR-biasing, the energy of SFQ circuits can be reduced by a factor of 20, giving SFQ circuits a performance advantage over CMOS circuits by more than two orders of magnitude [14].…”
Section: Discussionmentioning
confidence: 99%
“…This reduces the advantage of the SFQ shift-register memories in terms of the low-power consumption if we take into account the cooling cost. In order to reduce the static power consumption of the SFQ circuits, LR-biasing SFQ circuits have been investigated [6,7], where the bias resistances for SFQ circuits are replaced with large bias inductances with small bias resistance. In this study, we developed a low-power SFQ shift-register memory using the LR-biasing technique to show its effectiveness in large-scale SFQ circuits.…”
Section: Introductionmentioning
confidence: 99%